2015
DOI: 10.1039/c5ra09785a
|View full text |Cite
|
Sign up to set email alerts
|

One-pot template-free synthesis of heterophase BiVO4microspheres with enhanced photocatalytic activity

Abstract: 5One-pot template-free hydrothermal method was developed for the fabrication of BiVO 4 microsphere with tetragonal-monoclinic heterophase structure. XRD and HRTEM characterizations confirmed the formation of heterophase structure. It was found that the molar ratio of Bi/V and hydrothermal time were critical parameters in the yield of the spherical morphology and heterophase structure. Benefiting from the unique morphology and existence of heterophase, the as-prepared BiVO 4 microsphere exhibited 10 improved ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…Monoclinic scheelite bismuth vanadate (m-s BiVO 4 ), a p-type semiconductor with a direct band gap (E g ) of 2.4 eV, has generated considerable interest as a visible light-responsive photocatalyst. [1][2][3][4] Reportedly, different morphologies of monoclinically structured BiVO 4 crystallites, such as nanospheres, 5 nanorods, 6,7 nanoowers, 8 nanosheets, 9 nanotubes, [10][11][12] olive, 13,14 and hyperbranched, 15 have been clearly created by the hydrothermal or solvothermal technique. Nevertheless, the poor charge transport and weak surface adsorption properties associated with pristine BiVO 4 could cause prompt recombination of photogenerated electron-hole pairs, reducing its overall photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Monoclinic scheelite bismuth vanadate (m-s BiVO 4 ), a p-type semiconductor with a direct band gap (E g ) of 2.4 eV, has generated considerable interest as a visible light-responsive photocatalyst. [1][2][3][4] Reportedly, different morphologies of monoclinically structured BiVO 4 crystallites, such as nanospheres, 5 nanorods, 6,7 nanoowers, 8 nanosheets, 9 nanotubes, [10][11][12] olive, 13,14 and hyperbranched, 15 have been clearly created by the hydrothermal or solvothermal technique. Nevertheless, the poor charge transport and weak surface adsorption properties associated with pristine BiVO 4 could cause prompt recombination of photogenerated electron-hole pairs, reducing its overall photocatalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Usually these active species have different contributions in the photocatalysis process. For example, Hu et al [29] recently have reported the performance of the wellknown BiVO 4 photocatalyst. The improved photocatalytic activity was ascribed to the most effectively separation efficiency of photogenerated carriers generated in the BiVO 4 system.…”
Section: Photocatalytic Activity and Stabilitymentioning
confidence: 98%
“…O $À 2 and · OH had been detected in the suspension of BiVO 4 microsphere. Based on free-radical scavenging experiments, the decomposition of RhB was driven mainly by the participation of O $À 2 and a lesser extent by the participation of holes and · OH [29]. The experiment was conducted to investigate the photocatalytic species in this work.…”
Section: Photocatalytic Activity and Stabilitymentioning
confidence: 99%
“…This BiVO 4 sample showed a high phenol conversion (100%) within 90 min of natural sunlight illumination, which was related to the morphology of BiVO 4 (surface area = 10 m 2 /g). [6], (c) [22], (d) [29], (e) [30], (f) [31], (g) [32], (h) [33], (i) [34], and (j) [35]. An one-pot template-free hydrothermal method was developed for the fabrication of BiVO 4 microspheres with a tetragonal-monoclinic heterophasic structure [30].…”
Section: Sphere-like Bivomentioning
confidence: 99%
“…[6], (c) [22], (d) [29], (e) [30], (f) [31], (g) [32], (h) [33], (i) [34], and (j) [35]. An one-pot template-free hydrothermal method was developed for the fabrication of BiVO 4 microspheres with a tetragonal-monoclinic heterophasic structure [30]. The average diameter, bandgap energy, and BET surface area of the as-prepared The superior activity of the m-BiVO 4 sample was attributed to two reasons: (i) the BET surface area of the hierarchical hollow spheres was 10.6 m 2 /g, the higher surface area provided not only more surface reached by the visible light but also more active sites, which would result in good photocatalytic performance and (ii) the large hollow space inside the microspheres greatly decreased the density of m-BiVO 4 , thus rendering them to be easily suspended in water.…”
Section: Sphere-like Bivomentioning
confidence: 99%